Platelet glycoprotein IIb/IIIa receptor blockade in coronary artery disease - Suwaidi, Jassim Al (BioMed Central, 2001)
Glycoprotein IIb/IIIa inhibitors represent a new promising class of antiplatelet medications. Their use in acute coronary syndromes and for patients undergoing percutaneous coronary intervention has been the subject of a number of large controlled trials using both the intravenous and the oral forms. In this review, we present a systematic overview of these trials.